Biting the Hand that Feeds You? Exploring Whether (and How) Government Funding Constrains Charities’ Engagement in Public Policy - Cameron, John; Dicks, Heather; Swiss, Liam (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
This article examines relationships between federal government funding and reported spending by charities on what the Canada Revenue Agency defined as “political activities” over the period 2003–2017. Anecdotal evidence suggests that many charities in Canada see dependence on government funding by other charities as a factor that limits policy engagement. Comparative research generally suggests that government funding is positively associated with policy engagement by charities, but also that it channels charities away from outsider or contentious forms of advocacy toward less confrontational, insider strategies. The CRA data on political activities analyzed here adds important insights because it tracks outsider advocacy involving public calls to action, which government funding is expected to constrain. This analysis finds that charities with federal funding were more likely to report political activities than those with no federal funding, but only to a point and with important differences based on the size of charities.